2019
DOI: 10.1016/j.jpeds.2018.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Erythromelalgia and SCN9A Mutations: Systematic Review and Single-Center Case Series

Abstract: Objectives. To evaluate the clinical features of erythromelalgia in childhood associated with gainof-function SCN9A mutations that increase activity of the Na v 1.7 voltage-gated sodium channel we: i) conducted a systematic review of pediatric presentations of erythromelalgia related to SCN9A mutations; and ii) compared pediatric clinical presentations of symptomatic erythromelalgia, with or without SCN9A mutations. Study Design PubMed, Embase, and PsycINFO Databases were searched for reports of IEM in childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 104 publications
(160 reference statements)
3
30
0
Order By: Relevance
“…In the year 2000, Davis et al reported that 63% of EM patients had small fiber neuropathy, but it was not until 2004 that a mutant voltage-gated sodium channel (VGSC) 'Nav 1.7' encoded by SCN9 gene was discovered [23,24]. Since then, research has targeted the relationship between pain perception and VGSCs in sensory neurons, especially Nav1.7, Nav1.8 and Nav1.9 encoded by SCN9, SCN10 and SCN 11 genes respectively [24,25,26]. In a systemic review of pediatric population, 15 different SCN9A gene variants were found in 25 children with EM [25].…”
Section: Discussionmentioning
confidence: 99%
“…In the year 2000, Davis et al reported that 63% of EM patients had small fiber neuropathy, but it was not until 2004 that a mutant voltage-gated sodium channel (VGSC) 'Nav 1.7' encoded by SCN9 gene was discovered [23,24]. Since then, research has targeted the relationship between pain perception and VGSCs in sensory neurons, especially Nav1.7, Nav1.8 and Nav1.9 encoded by SCN9, SCN10 and SCN 11 genes respectively [24,25,26]. In a systemic review of pediatric population, 15 different SCN9A gene variants were found in 25 children with EM [25].…”
Section: Discussionmentioning
confidence: 99%
“…QST includes evaluation of small and large fibre function, with a range of stimulus modalities applied at varying intensities to assess detection and pain/discomfort thresholds. Expressing different modalities as Z-score differences from control measures allows group [31] or individual [34] profiles to be plotted independent of the measurement parameter ( Fig. 1b (i)).…”
Section: Examination and Evaluation Of Somatosensory Functionmentioning
confidence: 99%
“…Altered somatosensory function has been identified in a range of paediatric conditions associated with peripheral nerve injury, including chemotherapy-induced neuropathy in cancer survivors [35], erythromelalgia [34], prior surgery [31], and subclinical signs of diabetic neuropathy [36]. In adults with peripheral neuropathic pain, three distinct sensory profiles that may predict mechanism and improved treatment efficacy for subclasses of anti-neuropathic medication have been identified: sensory loss (denervation and spontaneous pain due to ectopic action potentials proximal to injured nociceptors; greater response to anti-depressants); thermal hyperalgesia (peripheral sensitisation with low threshold and spontaneous activity in 'irritable nociceptors'; predicted efficacy with sodium channel blocker and moderate response to anti-depressant or gabapentinoid); and mechanical hyperalgesia (sensitisation and spontaneous activity in peripheral and/or central nervous system; predicted efficacy with gabapentinoid) [37,38].…”
Section: Examination and Evaluation Of Somatosensory Functionmentioning
confidence: 99%
See 2 more Smart Citations